Socio-Economic Study of Traditional Fishermen in Sayolo Village Papua as a Basis for Affirmative Welfare Programs - Anna Dara; Hendry Jems Yoel Aidore; La Ode M Aslan (Politeknik Negeri Sambas, 2026)
Traditional fishers in coastal areas of Papua face limitations in fishing technology, access to capital, and market access, which contribute to the low welfare levels of fishing households. This study aimed to analyze the socioeconomic conditions of traditional fishers in Sayolo Village, Teminabuan District, South Sorong Regency, and to formulate the need for affirmative programs to improve their welfare. This study employed a descriptive qualitative and quantitative approach through field observations, in-depth interviews, questionnaires administered to 30 fisher household heads, and Focus Group Discussions (FGDs) involving relevant stakeholders. The results showed that 70% of respondents worked as full-time fishers, with educational attainment predominantly at the elementary school level (53%). Average fish catches ranged from 30–45 kg per week during the peak fishing season and declined to 15–20 kg per week during unfavorable seasons. Net income ranged from approximately IDR 200,000 to IDR 650,000 per week, which remained below the Provincial Minimum Wage. Operational cost structures were dominated by fuel expenses, accounting for 45–55% of total costs, thereby increasing income vulnerability among fishers. Existing affirmative programs included fishing gear assistance, fish processing training, and village financial support; however, their implementation remained uneven. The policy implications suggest the need to strengthen fishers’ institutions, improve access to financial capital, provide post-harvest facilities, and promote the empowerment of coastal women based on local resource potential.